The Prevalence of Core Muscles Weakness and Fatigue in 18-to 25-Year-Old Medical College Students: Prevalence of Core Muscles Weakness and Fatigue - Ahmad, Gulzar; Shahzad, Areeba (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Core muscles play a significant role in the stability of the back spine, ribcage, and lumbopelvic region by influencing daily living activities and balance. Objectives: To investigate core muscles weakness among male and female medical college students aged 18-25 and to evaluate their core muscle endurance using the McGill core endurance tests. Also, to assess fatigue levels among participants using the Rating of Fatigue Scale (ROF). Methods: A total of 246 participants were recruited from Rashid Latif Medical College (RLMC) and Johar Institute of Professional Studies (JIPS), Lahore, using non-probability convenient sampling. The sample size was determined using Epitool software. To assess core muscle endurance, the McGill Core Endurance Test was administered. Additionally, the Rating of Fatigue Scale was used to evaluate fatigue levels among participants. Data were entered and analyzed using SPSS version 27.0. Numeric data are presented as mean and standard deviation. Results: 92.68% of participants exhibited core muscles weakness during the 60º Spinal Flexion Test, and 96.75% of participants exhibited core muscles weakness during the Side Plank Tests. Another Rating of fatigue is a prevalent issue among the participants, with only 10.2% reporting no fatigue. The majority of participants (43.5%) experienced mild fatigue, while a significant proportion (37%) reported moderate fatigue. Furthermore, 8.5% of participants experienced severe fatigue, and 0.8% reported the worst fatigue. Conclusions: It was concluded that a remarkably high prevalence of core muscles weakness was found among medical college students. Furthermore, failure to engage core muscles during daily activities likely contributes to this prevalent weakness.